2019
DOI: 10.1016/j.jhin.2019.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and impact of norovirus outbreaks in Norwegian healthcare institutions, 2005–2018

Abstract: The aim of this study was, for the first time, to describe in detail the epidemiology and impact of norovirus outbreaks in healthcare institituions (HCIs) in Norway to identify areas which may improve outbreak response. Methods: An analysis of all reported norovirus outbreaks in hospitals and long-term-care facilities (LTCFs) was carried out from week 34, 2005 to week 33, 2018. Seasonality, symptoms and number of cases among personnel and patients were described. Findings: A total of 20,544 cases, including 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…The number of coinfections in the present study is higher than in two distinct Italian and French pediatric studies where coinfections were only detected in 8.3% and 3.3% of virus-positive patients, respectively [14,15]. In these studies, viruses were mostly detected by EIA and ELISA and some of the differences season, fewer coinfections, and also many cases in adults, where family and small general outbreaks including foodborne outbreaks are well known to occur [16].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The number of coinfections in the present study is higher than in two distinct Italian and French pediatric studies where coinfections were only detected in 8.3% and 3.3% of virus-positive patients, respectively [14,15]. In these studies, viruses were mostly detected by EIA and ELISA and some of the differences season, fewer coinfections, and also many cases in adults, where family and small general outbreaks including foodborne outbreaks are well known to occur [16].…”
Section: Discussioncontrasting
confidence: 74%
“…Sapovirus had a unique age-specific profile with a modest number of infections occurring beyond 10 years of age. Norovirus had a completely different epidemiology with a long winter season, fewer coinfections, and also many cases in adults, where family and small general outbreaks including foodborne outbreaks are well known to occur [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inns et al described 566 AGE outbreaks in LTCF in North East England between 2016 and 2018 and norovirus was detected in 64% of outbreaks with a pathogen identi ed26 . Steele et al studied 7,094 norovirus outbreaks between 2009 and 2017 in United States of which 5,335 (75%) occurred in LTCF27 and Espenhain et al found that 77% of norovirus outbreaks in Norway between 2005 and 2018 were in LTCF28 .A seasonal distribution was observed, with most of outbreaks occurring in autumn and winter. Our results are consistent with previous ndings by other authors indicating a seasonality of norovirus disease4,28 .…”
mentioning
confidence: 99%